First-principles calculation on the relationships of h-WC/γ-Fe interface. (December 2018) - Shi, Zhijun; Liu, Sha; Zhou, Yefei; Yang, Qingxiang
Abstract: The adhesive work, interfacial energy, charge density, charge density difference and layer-projected density of states (DOS) of h-WC(0001)/γ-Fe (111) interfaces were calculated by the first principles method. The structural stability of the interfaces was researched by the adhesive work and interfacial energy of h-WC(0001)/γ-Fe (111) interfaces. The interfacial electronic structures were analyzed by charge density and charge density difference, and the interface bonding characteristics were revealed by Mulliken charges and layer-projected DOS of the interface models. The results show that the work of adhesion for C-terminated HCP stacking interface structure is the largest ( W ad  = 3.44 J/m 2 ), which indicates that the reversible work used to separate the C-HCP interface into two free surfaces is the largest in all interfaces. When Δμc changes from −0.37 eV to 0 eV, the interfacial energy of C-terminated HCP stacking interface structure is in the range of 1.186–1.588 J/m 2, while that of W-terminated HCP stacking interface structure is in the range of 1.142–1.541 J/m 2 . When −0.165 eV < Δμc < 0 eV, the interfacial energy of C-terminated HCP stacking interface is smaller than that of W-terminated one, which indicates the C-terminated HCP stacking interface is more stable. When −0.37 eV < Δμc < -0.165 eV, W-terminated HCP stacking interface turns to be more stable than C-terminated one. The total charge density of C-terminated HCP stacking interface is much larger than that of W-terminated one, and the degree of ionization of C-terminated HCP interface is also higher. The bonding of C-terminated HCP stacking interface is a mixture of covalent bond, ionic bond and metallic one, while that of W-terminated HCP stacking interface is a mixture of covalent bond and metallic one. Graphical abstract: Image 1 Highlights: Work of adhesion W ad and interfacial energy γ of h-WC(0001)/γ-Fe (111) interfaces were calculated. Interfacial electronic structures between h-WC and γ-Fe were analyzed. Interface bonding characteristics were revealed by Mulliken charges and layer-projected DOS. The bonding strength between WC particle and various substrates was compared.